2010 IEEE International Geoscience and Remote Sensing Symposium 2010
DOI: 10.1109/igarss.2010.5653075
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in sparse hyperspectral unmixing

Abstract: This paper explores the applicability of new sparse algorithms to perform spectral unmixing of hyperspectral images using available spectral libraries instead of resorting to well-known endmember extraction techniques widely available in the literature. Our main assumption is that it is unlikely to find pure pixels in real hyperspectral images due to available spatial resolution and mixing phenomena happening at different scales. The algorithms analyzed in our study rely on different principles, and their perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The convergence of the repeat process can be ensured by the Split Bregman algorithm, and the convergence of the whole algorithm is proved in Xu et al (2010). As ASC is critical (Iordache et al 2010b), we can set c = 0 in line 5.2 to easily discard it. The parameter λ is to keep the balance between the sparsity of the abundances and the residual of the least square term.…”
Section: Our Proposed Methodsmentioning
confidence: 99%
“…The convergence of the repeat process can be ensured by the Split Bregman algorithm, and the convergence of the whole algorithm is proved in Xu et al (2010). As ASC is critical (Iordache et al 2010b), we can set c = 0 in line 5.2 to easily discard it. The parameter λ is to keep the balance between the sparsity of the abundances and the residual of the least square term.…”
Section: Our Proposed Methodsmentioning
confidence: 99%
“…A spectral unmixing method for a hyperspectral image based on sparse decomposition was proposed in Ref. 10. The redundant dictionary was trained by the spectral library samples, dependence on end member extraction accuracy, as done by other algorithms was avoided, and good results were obtained.…”
Section: Related Backgroundmentioning
confidence: 99%
“…Thus, any pixel curve can be represented by a combination of several atoms. Some researches 10 suggested that by redundant dictionary based sparse decomposition, the atoms of the trained redundant dictionary reflected the spectral features of the imaging materials. Most of the atoms were consistent with a certain spectral curve of the material.…”
Section: Principle Of Pixel Curve Based Sparse Decomposition Of the Hmentioning
confidence: 99%
“…The mixture problem will seriously influence the efficiency of hyperspectral remote sensing information processing. There are two mixture models, named linear mixing and nonlinear mixing [1]. The linear mixture model (LSMM) assumes minimal secondary reflections and multiple scattering effects in the data collection procedure [2], and hence the measured spectra can be expressed as a This work has been supported by the National Natural Science Hyperspectral unmixing is a typical problem of blind source separation, as the collected mixed pixels, endmember signatures and corresponding proportions can be seen as the observations, mixing matrix and sources respectively.…”
Section: Introductionmentioning
confidence: 99%